DIGITAL MARKETING OF COFFEE BASED ON THE UMMA PANDE COMMUNITY IN SOUTHWEST SUMBA REGENCY, EAST NUSA TENGGARA - Pathmi Noerhatini; Amanna Dzikrillah Al Hakim; Dicky Rezadi Munaf (Journal of Rural Development and Applied Technology, 2024)
Some coffee farmers in Southwest Sumba Regency, East Nusa Tenggara (NTT) province are members of a community known as Umma Pande (Smart House). Umma Pande symbolizes local wisdom, in which farmers have cultural ties and maintain community brotherhood even though administrative areas are separated. Community-based community empowerment with its local wisdom is interesting to study because there is local wisdom that will drive the success of community empowerment programs. Meanwhile, the obstacle faced by coffee farmers is increasing sales of coffee products outside the region. Therefore, a technology is needed, including digital marketing. Therefore, we are doing community service in three subdistricts (East Weweha, Central Weweha and West Weweha), Southeast Sumba Regency, to identify the potential and opportunities for coffee farmers to market through digital marketing. The conducted from March until November 2022. The results of identification of potential coffee plantations and farmers showed that the management of robusta coffee plantations by coffee farmers used local wisdom, namely the values ​​or behaviour of local wisdom in interacting with the environment in which they live. Coffee farmers experience two obstacles, namely competitiveness and product connectivity. The solution to this problem was to increase collaboration networks between community members and digital marketing. The marketing tool was using social media and website.